Worker Reciprocity and the Returns to Training: Evidence from a Field Experiment - Jan Sauerman; Muhammad Baiqun Isbahi (Majapahit Journal of Islamic Finance and Management, 2023)
Is there a correlation between reciprocal workers and higher returns to employer-sponsored training? The study employed a field experiment that utilized random assignment to training, along with the collection of survey data on workers' reciprocal tendencies. The findings of the study indicate that workers who exhibit reciprocal behavior are more likely to reciprocate their employers’ expenditures in training by demonstrating higher levels of performance after completing the training program. The findings of this study remain consistent even after accounting for observed personality traits and worker-fixed effects. These results indicate that individuals respond to the firm's investment in human capital by exerting greater effort, aligning with theoretical models that propose a reciprocal relationship between gift exchange in the workplace. This discovery offers an alternate justification for corporate training investments, notwithstanding the potential danger of employee poaching.